On the relation between 2 and ∞ in Galois cohomology of number fields - Schmidt, Alexander (Compositio mathematica, 2002)
We remove the assumption 'p≠ 2 or k is totally imaginary' from several well-known theorems on Galois groups with restricted ramification of number fields. For example, we show that the Galois group of the maximal extension of a number field k which is unramified outside 2 has finite cohomological 2-dimension (also if k has real places).
Published online: 04 December 2007
Gesehen am 04.05.2018